2018
DOI: 10.1371/journal.pone.0193278
|View full text |Cite
|
Sign up to set email alerts
|

Early measurement of interleukin-10 predicts the absence of CT scan lesions in mild traumatic brain injury

Abstract: Traumatic brain injury is a common event where 70%–90% will be classified as mild TBI (mTBI). Among these, only 10% will have a brain lesion visible via CT scan. A triage biomarker would help clinicians to identify patients with mTBI who are at risk of developing a brain lesion and require a CT scan. The brain cells damaged by the shearing, tearing and stretching of a TBI event set off inflammation cascades. These cause altered concentrations of a high number of both pro-inflammatory and anti-inflammatory prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…The four proteins—S100B, GFAP, H-FABP and IL-10—have all previously been identified for their potential to differentiate CT-positive and CT-negative mTBI patients, confirming the results found here. [ 10 , 16 , 19 , 41 ] The proteins have been shown to be released from or leak out of different types of injured cells. Indeed, S100B and GFAP leak from injured astrocytes, H-FABP leaks from endothelial cells and neuron cell bodies, whereas Il-10 is expressed by monocytes and macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The four proteins—S100B, GFAP, H-FABP and IL-10—have all previously been identified for their potential to differentiate CT-positive and CT-negative mTBI patients, confirming the results found here. [ 10 , 16 , 19 , 41 ] The proteins have been shown to be released from or leak out of different types of injured cells. Indeed, S100B and GFAP leak from injured astrocytes, H-FABP leaks from endothelial cells and neuron cell bodies, whereas Il-10 is expressed by monocytes and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 13 proteins—H-FABP, the matrix metalloproteinases 1, 3 and 9 (MMP-1, MMP-3 and MMP-9 respectively), the vascular and intravascular cell adhesion molecules (VCAM and ICAM respectively), IL-10, the inflammatory proteins serum amyloid A (SAA) and C-reactive protein (CRP), the oxidative stress proteins glutathione S-transferase pi (GSTP), nucleoside diphosphate kinase A (NKDA) and peroxiredoxin 1 (PRDX1) and the parkinson disease protein 7 (PARK7/DJ-1)—were chosen. [ 10 , 16 , 23 , 32 37 ] These proteins were investigated for their individual performances as CT-scan triage biomarkers in mTBI patients with a GCS score of 15 and at least one clinical symptom. The best-performing proteins were then compared with the two most studied mTBI biomarkers: S100B and GFAP.…”
Section: Introductionmentioning
confidence: 99%
“…A biomarker especially for triage of patients with mTBI to guide diagnostic procedures is warranted; however, previous studies have demonstrated low specificity for inflammatory markers for predicting, for example, CT findings. 51 Thus, further studies are needed to investigate if the demonstrated inflammatory state is caused by neuroinflammation, and what are the clinical implications of prolonged inflammation with INFLAMMATION PERSISTS ONE YEAR AFTER MTBI outcome, such as post-concussion syndrome, and potential for manipulating it for improved outcome.…”
Section: Implications For Diagnosis Follow-up and Therapymentioning
confidence: 99%
“…Clinically, after TBI different aspects of the inflammatory response are monitored, mainly by assessing markers of inflammation in different body fluids and sometimes tissue . By detecting cytokine profiles in blood, which is easily accessible, it is possible to both separate healthy individuals from patients with radiological visible injury , and predict outcome months after injury . However, detection of inflammatory markers in the cerebrospinal fluid (CSF) is often more specific for brain injuries as compared to blood.…”
Section: Human Pathology Of Ctementioning
confidence: 99%